Globalizacja i ruchy myślenia alternatywnego – o potrzebie zorientowania społeczeństwa na odpowiedzialne współuczestnictwa i współdziałania - Cybal-Michalska , Agnieszka (Studia Edukacyjne, 2018)
Contemporary world has become a global ecumene. The theory of globalization as approached by R. Robertson invokes the world conceptualization which assumes reducing the tension between the dichotomous tendencies. Unification and diversification are complementary processes, they are mutually influential and essential for the contemporary stage of development of the global society. The paradigm of globalization on the social and cultural plane is revealed in the binary scheme of extremes, such as: decontextualization and recontextualization, decomposition and recomposition, deteritorialization and re-teritorialization, transculturation and internalization. The contemporary anti-globalist movement is a reflection of ideological opposition. The criticism of globalization remains in close connection to an increasingly lively discussion regarding alternatives to globalization. Specificity of the quality of global cultural ecumene reveals the need to shape and improve the orientation towards responsible participation and cooperation in the changing and co-dependent global society.